Oxidation behavior of Si3N4 fibers derived from polycarbosilane. (15th May 2018) - Li, Siwei; Li, Yongcai; Xiao, Hongrui; Li, Xiangdong; Wang, Qi; Tang, Ming; Tu, Huibin; Huang, Jinqiu; Chen, Lifu; Yu, Zhiyang
Highlights: Oxidation kinetics of the PCS-Si3 N4 fiber is reaction-controlled at 800 °C. Oxidation kinetics of the fiber is diffusion-controlled at above 1000 °C. Coating with four sub-layers is formed on the Si3 N4 fiber by oxidation in wet air. The Si3 N4 fiber has faster oxidation kinetics than the other known Si3 N4 ceramics. Abstract: Si3 N4 fibers prepared from polycarbosliane are exposed in dry and wet air respectively from 800 to 1300 °C for up to 1 h. After dry air oxidation, an uniform SiO2 coating doped with nitrogen is formed on fiber surface. However, the coating obtained in wet air is much thicker with more complex microstructure containing sub-layers of N-doped SiO2, near stoichiometric Si3 N4 and graphite-like nanoribbons. Activation energy for oxidation in wet and dry air is determined as 108 and 152 kJ mol −1, respectively. Both of the values are lower than the known Si3 N4 materials with Ea of 259–485 kJ mol −1 .